The influence of tourism facilities and attractions on revisit intentions with visitor satisfaction as an intervening variable: A study on Kampung AEWO Mulyaharja Bogor - Masriah, Imas; Ingkadijaya, Rahmat; Mumin, Adhi Trirachmadi (International Journal of Applied Sciences in Tourism and Events, 2024)
This study aims to analyze the influence of tourism facilities and attractions on visitors' revisit intentions, with visitor satisfaction serving as an intervening variable, focusing on Kampung AEWO Mulyaharja, Bogor. The research method used is a quantitative approach using PLS SEM (Partial Least Squares Structural Equation Modeling). The population of this study consists of visitors who have visited AEWO Mulyaharja Village in Bogor at least once, with a total sample of 366 respondents. Sampling was conducted using a combination of probability sampling and purposive sampling techniques, with a minimum respondent age of 18 years. The research findings indicate that 1) tourism facilities directly influence visitor satisfaction. 2) tourist attractions have a direct influence on visitor satisfaction. 3) tourism facilities have a direct influence on revisit intention. 4) tourist attractions have a direct influence on revisit intention. 5) visitor satisfaction has a direct influence on revisit intention. 6) tourism facilities significantly indirectly influence revisit intention, with visitor satisfaction as an intervening variable. 7) tourist attractions significantly indirectly influence revisit intention with visitor satisfaction as an intervening variable. The results of this study can serve as a guide for the management of tourist villages, such as AEWO Mulyaharja Village in Bogor, in developing facilities and services that cater to visitors' needs.